The cotton manufacturing industry of the United States - Copeland, Melvin Thomas (Harvard university, 1917)
This volume from the Cornell University Library's print collections was scanned on an APT BookScan and converted to JPG 2000 format by Kirtas Technologies. All titles scanned cover to cover and pages may include marks, notations and other marginalia present in the original volume.